Challenges and Progress in Ensuring the Right to Be Heard and the Best Interests of Children Seeking International Protection - Kanics, Jyothi (Refuge: Canada's Journal on Refugees, 2016)
Societal attitudes towards children significantly limit the extent to which they are able to realize their rights and can contribute to discrimination against children. Fortunately, legislative reform as well as changes in policies and practices are slowly leading to progress for children, in line with the Convention on the Rights of the Child. Child-sensitive procedures for children seeking international protection are being developed and implemented. It is crucial that these systems be strengthened so that durable solutions for children and families are secured without discrimination and in line with the best interests of the children concerned.